Draft genome sequence of Bacillus azotoformans MEV2011, a (Co-) denitrifying strain unable to grow with oxygen. Issue 1 (December 2015) - Nielsen, Maja; Schreiber, Lars; Finster, Kai; Schramm, Andreas
Abstract Bacillus azotoformans MEV2011, isolated from soil, is a microaerotolerant obligate denitrifier, which can also produce N2 by co-denitrification. Oxygen is consumed but not growth-supportive. The draft genome has a size of 4.7 Mb and contains key genes for both denitrification and dissimilatory nitrate reduction to ammonium.